Symposium 9: Methodologies for researching the learning in Networked Learning: Symposium Introduction - Alexander, Shirley; Booth, Shirley (Proceedings of the International Conference on Networked Learning, 2008)
Understanding the educational power of Networked Learning presents a significant challenge. Intensive scrutiny of teaching approaches has been given far more attention in educational research than careful consideration of learning gains. Now, in Networked Learning, we are refining and deploying newly available technologies in large part on the basis of what we are technically able to do and not necessarily because of the worth of such opportunities for learning. A core reason for this neglect is the lack of strongly theorised positions on learning and therefore on networked learning research. This symposium presents three approaches by which this lack of a learning research basis for Networked Learning might be redressed. Each paper presents a particular theoretical view of learning. Then, by case study, methodological implications of that theory for researching the educational significance of Networked Learning are described and demonstrated. Schaverien and Alexander assert that the late C20th and C21st has brought advances in the natural sciences and in ways of thinking about complex dynamic self-organising systems, yielding a powerful, state-of-the-art (generative) learning theory, which they then describe. They focus on how a research methodology for investigating learning (including Networked Learning) emerges from this generative learning theory, illustrating it with a recent Australian Research Council (ARC) funded project (in which both authors were Chief Investigators). They report on the power of this methodology to elicit important insights into the learning that occurred in that project and speculate on its broader research potential. Booth perceives her paper as a complement to what she sees as the individual orientation of the first paper and the social orientation of the third paper in this symposium. She presents phenomenography and variation theory as empirical and theoretical approaches to research on learning, in particular as applicable to networked learning, describing their epistemological, ontological and methodological underpinnings. She uses three studies as examples for a discussion of the research questions that can be asked in empirical studies, the approaches to data collection and/or data generation, and analysis, and the presentation of results in wider frameworks that expand research possibilities. Here, individual learners contribute only fragments of the data that is to be analysed as a whole pool, and results are presented at the collective level of the pool. Fox draws attention to the recent resurgence of interest in ethnomethodology from management and organization theorists, at least. He argues that within the ‘practice turn’ there is now a strong thread of ethnomethodologically informed ethnographic studies. He argues that rather than being aggregated to formulate an overarching theory of workplace practices or learning (as ethnographic studies have been), each ethnomethodological study produces a unique insight into the specifics of situated practice. He illustrates his argument by discussing a case study of audio-visual learning resources provided for science educators via a national programme of teleconferences. These three papers provoke consideration of commonalities and differences in their approaches to researching networked learning, and of whether it is possible or fruitful to work towards a shared theoretical position.